THE DIRECT IMPACT OF CLASSIC AND MODERN THEORIES OF CIVIL SOCIETY ON POLITICS, ECONOMY, SOCIAL AND SPIRITUAL SPHERES - Mukhimjon Khirgizboev; Nosirbekov Kozimbek Sunnatbek o`g`li (Scholars Digest Publishing, 2023)
The origin, development and introduction of the concept of civil society into the world of science covers many years. The emergence of this term in science as a civil society and its integration in the cross-section of fields is related to classical and modern theories. If the citizen is studied in science as a concept that belongs to the state, the main influencing factor is the scientific research conducted on researching what kind of relations it has with the society and bringing it into science as a novelty. Society is evaluated as a very large group, and it is concluded that it is a link closely related to the state, but it is not a concept related to the state. Exactly, a citizen who belongs to the state lives in the society and acts as the main link between the state and society. The article deals with these issues.
Keywords: civil society, politics, economy, society, spiritual behavior, theories of civic characteristics, classical and modern theories.